What is the equation of the tangent line of #f(x)=sqrt(x^2-4x+7)/(x-1)# at #x=3#?

Answer 1

#y = -1/4x + 7/4#

Start by finding the y-coordinate.

#f(3) = sqrt(3^2 - 4(3) + 7)/(3- 1) = sqrt(4)/2 = 1#
Differentiate using the quotient rule. Let #f(x) = (g(x))/(h(x))#, with #g(x) = sqrt(x^2 - 4x + 7)# and # h(x) = x - 1#.
We use the chain rule to differentiate #g(x)#:
Let #y = u^(1/2)# and #u = x^2 - 4x + 7#. Then #dy/(du) = 1/(2u^(1/2))# and #(du)/dx = 2x - 4#.
#g'(x)= dy/(du) * (du)/dx#
#g'(x) = 1/(2u^(1/2)) * 2x - 4#
#g'(x) = (2x- 4)/(2sqrt(x^2 - 4x + 7))#
#g'(x) = (2(x - 2))/(2sqrt(x^2 - 4x + 7))#
#g'(x)= (x- 2)/sqrt(x^2 - 4x + 7)#

Now use the quotient rule:

#f'(x) = (g'(x) * h(x) - g(x) * h'(x))/(h(x))^2#
#f'(x) = ((x - 2)/sqrt(x^2 - 4x + 7)(x - 1) - sqrt(x^2 - 4x + 7)(1))/(x - 1)^2#
#f'(x) = ((x^2 - 2x - x + 2)/sqrt(x^2 - 4x + 7) - sqrt(x^2 - 4x + 7))/(x- 1)^2#
#f'(x) = ((x^2 - 3x + 2 - (x^2 - 4x + 7))/sqrt(x^2 - 4x + 7))/(x - 1)^2#
#f'(x) = (x - 5)/(sqrt(x^2 - 4x + 7)(x- 1)^2#
The slope of the tangent line can be obtained by evaluating the point #x = a# into the derivative.
#f'(3) = (3 - 5)/(sqrt(3^2 - 4(3) + 7)(3 - 1)^2#
#f'(3) = -2/(2(4))#
#f'(3) = -1/4#

The equation of the tangent is therefore:

#y - y_1 = m(x - x_1)#
#y- 1 = -1/4(x - 3)#
#y - 1 = -1/4x + 3/4#
#y = -1/4x + 7/4#

Hopefully this helps!

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the equation of the tangent line of f(x) = sqrt(x^2 - 4x + 7)/(x - 1) at x = 3, we need to find the derivative of f(x) and evaluate it at x = 3. The derivative of f(x) can be found using the quotient rule:

f'(x) = [(x - 1)(2x - 4) - (x^2 - 4x + 7)(1)] / (x - 1)^2

Simplifying this expression gives:

f'(x) = (2x^2 - 6x + 4 - x^2 + 4x - 7) / (x - 1)^2 = (x^2 - 2x - 3) / (x - 1)^2

Now, we can evaluate f'(x) at x = 3:

f'(3) = (3^2 - 2(3) - 3) / (3 - 1)^2 = (9 - 6 - 3) / 2^2 = 0

The slope of the tangent line at x = 3 is 0. To find the equation of the tangent line, we need a point on the line. We can use the point (3, f(3)).

f(3) = sqrt(3^2 - 4(3) + 7)/(3 - 1) = sqrt(9 - 12 + 7)/2 = sqrt(4)/2 = 2/2 = 1

Therefore, the point on the tangent line is (3, 1). The equation of the tangent line can be written in point-slope form:

y - y1 = m(x - x1)

Using the point (3, 1) and the slope m = 0, we have:

y - 1 = 0(x - 3) y - 1 = 0 y = 1

Hence, the equation of the tangent line of f(x) = sqrt(x^2 - 4x + 7)/(x - 1) at x = 3 is y = 1.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7